Validity And Practicality E-Book Based On Android Of Materials Structure And Function Of Animal Tissue 11th Grade Senior High School - Setiawan, Dona; Razak, and Abdul (IJIS Edu : Indonesian Journal of Integrated Science Education, 2020)
Education is one of the supporting factors to improve the quality of human resources and is shown by the higher standard of education and along with progress in the 21st century. In this century, we know the term generation millennial, in general, it is found among students who are approaching adulthood and already have many communication devices inform of the smartphone. The use of a smartphone as educational media that is not maximally used.-based electronic teaching materials for android students is not available until now although there are currently very few to use. The purpose of this study is to produce an e-book based on android the structure and function of animal tissue that is valid and practical. This type of research is research and development. The method used in this research development is to use a plomp model. The object of the study consisted of one biology teacher and 35 students of 11th grade science Senior High Public School 3 Padang. Based on the results of this study produced e-book based on android on the material structure and function of animal tissue that showed an average value of 86.56% (very valid) based on validator ratings, practicality assessments by biology teachers showed an average value of 96.25% (very practical) and practicality assessment of field tests by 35 students obtained an average value of 86.66% (very practical). So, it can be concluded that the e-book based on android on the material structure and functions of animal tissue developed is very valid and very practical to use.